Factors Affecting Romantic Relationship Satisfaction of University Students (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background/Objectives: The purpose of this study was to identify the factors affecting romantic relationshipsatisfaction of university studentsMethods/Statistical analysis: This study was conducted with 187 students from four universities in citiesand provinces nationwide. Data were collected from September to October 2019 using a self-administeredquestionnaire. Collected data were analyzed through the stepwise regression analysis using the SPSSstatistics program.Findings: The final regression model showed that self-esteem, anxiety attachment, and avoidance attachmentwere significant predictors related to romantic relationship satisfaction in university students and explained34.7% of the variance in romantic relationship satisfaction.Improvements/Applications: The university student period is a time to form an adult attachment, therebypreparing for a happy marriage in the future by increasing the romantic relationship satisfaction. Therefore,it is necessary to develop and apply the educational programs that can increase self-esteem and positiveheterosexual relationship for university students.